Research on spatial-temporal distribution characteristics and influencing factors of national cultural relics protection units in Shanxi Province - Liu, Wenhua; Liang, Shaoru; Wei, Shuang (International Journal of Social Sciences and Public Administration, 2024)
This study takes 530 national cultural relics protection units in Shanxi Province as the research object, and uses mathematical statistics and GIS spatial analysis methods to explore the spatial-temporal distribution characteristics and influencing factors of national cultural relics protection units in Shanxi Province. The results show that there are differences in the number of national cultural relics protection units in Shanxi Province during different historical periods, showing a trend of first increasing and then decreasing. The formation of various types of national cultural relics protection units has a relatively concentrated historical period. The distribution center of national cultural relics protection units in Shanxi Province has changed with historical periods, showing a migration characteristic in the direction of south northeast southeast south southeast northwest northeast. The national cultural relics protection units in Shanxi Province are in a clustered distribution state, and the clustering characteristics of different types of national security units are also different. The gradient distribution characteristics of national cultural relics protection units in different administrative cities are obvious. The spatial and temporal distribution of national cultural relics protection units in Shanxi Province is influenced by factors such as topography, river systems, and transportation.